The Dynamic Interaction between Extracellular Matrix Remodeling and Breast Tumor Progression - Jorge Martinez; Patricio C. Smith (Cells, 2021)
Desmoplastic tumors correspond to a unique tissue structure characterized by the abnormal deposition of extracellular matrix. Breast tumors are a typical example of this type of lesion, a property that allows its palpation and early detection. Fibrillar type I collagen is a major component of tumor desmoplasia and its accumulation is causally linked to tumor cell survival and metastasis. For many years, the desmoplastic phenomenon was considered to be a reaction and response of the host tissue against tumor cells and, accordingly, designated as “desmoplastic reaction”. This notion has been challenged in the last decades when desmoplastic tissue was detected in breast tissue in the absence of tumor. This finding suggests that desmoplasia is a preexisting condition that stimulates the development of a malignant phenotype. With this perspective, in the present review, we analyze the role of extracellular matrix remodeling in the development of the desmoplastic response. Importantly, during the discussion, we also analyze the impact of obesity and cell metabolism as critical drivers of tissue remodeling during the development of desmoplasia. New knowledge derived from the dynamic remodeling of the extracellular matrix may lead to novel targets of interest for early diagnosis or therapy in the context of breast tumors.